(untitled) (Gestión y Gerencia, 2025)
The objective of the research addressed was to present a procedure for outlining the charcoal value chain as a basis for accounting management for the calculation of profits in the Agroforestal company of Pinar del Río, Cuba. In which a theoretical methodological analysis is made of each of the definitions used to justify the results obtained, this being quantitative and qualitative in nature. The main limitations were identified as the lack of documentation necessary to identify those activities that generate added value to obtain the expected profits through the value chain, as well as the non-recognition of the value chain instrument to achieve the benefits by the company. The calculation of profits through each of the links defined by the value chain was demonstrated through the procedure, thus defining those that consume more resources than others and which add value to the process. It is concluded that to achieve efficiency in the environment of business relations and thus achieve a greater productive chain, the application of the proposed procedure is necessary to visualize its results.